The roles of intrinsic motivation and capability-related factors in cognitive effort-based decision-making - Randez, Alyssa; Hélie, Sébastien (Frontiers in Psychology, 2024)
Individual differences in cognitive effort-based decision-making can be used to reveal human motivations to invest effort into a given task. Preferences among options that differ by dimensions related to demand levels (i.e., the interaction of task characteristics and performance measures) are also heavily influenced by how likely a person can succeed at a given option. However, most existing cognitive effort-based research has focused primarily on demand-related factors, leading to confounding inferences about the motivation behind these choices. This study used an adaptive algorithm to adjust relative demand levels for three cognitive tasks to investigate general and individual differences in demand preferences. The results highlight an overall pattern of individual differences in intrinsic motivation to perform challenging tasks, supporting research that found cognitive effort aversive to some but attractive to others. These results suggest that relative demand levels and intrinsic task factors drive the motivation to select an action.